2018
DOI: 10.12659/msm.907588
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical Outcomes in Elderly Chinese Patients with Multiple Myeloma: A Single-Center Experience

Abstract: BackgroundRecently, improvement in overall survival (OS) was demonstrated in elderly patients with multiple myeloma (MM). Our aim here was to analyze treatment outcomes in elderly Chinese patients with MM in real-world practice.Material/MethodsThis retrospective study enrolled 122 newly diagnosed MM patients ages 65–84 between January 2007 and December 2015 in a single hematology department.ResultsThe median age of patients was 70.5 years. The median OS period of the entire cohort was 33 months; the 5-year OS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In this study, the male-to-female ratio was 1. reported in other studies in China (19,20). In terms of clinical efficacy, the remission rates of VGPR were 18.4% and 15.9% in the study and control groups, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…In this study, the male-to-female ratio was 1. reported in other studies in China (19,20). In terms of clinical efficacy, the remission rates of VGPR were 18.4% and 15.9% in the study and control groups, respectively.…”
Section: Discussionsupporting
confidence: 46%
“… 27 On the contrary, the Chinese have demonstrated better OS in female vis-à-vis male (40 v 28 months, respectively). 28 …”
Section: Discussionmentioning
confidence: 99%
“…As known, age is one of the most important prognostic factors in the treatment of MM. 16 A published study reported that approximately one-third of MM patients were older than 75 years at the time of diagnosis. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics and clinical data were collected and assessed. Patients were stratified by Durie-Salmon stage, International Staging System (ISS) disease stage and revised-ISS (R-ISS) stage respectively, and the risk stratification based on International Myeloma Working Group (IMWG) criteria-high risk mutation including del (17p), t (4,14) and t (14,16). 11,12 RRMM patients were identified by IMWG consensus.…”
Section: Patientsmentioning
confidence: 99%